Analysis of Grade X Physics Textbooks on the Basic Measurement Material from the Nature of Science Perspective - Huwaida, Junita Insyirah; Saparini, Saparini (FKIP ULM, 2023)
Issues related to the quality of textbooks are often a topic of discussion in science. However, in various education systems, some textbooks have effectively incorporated the nature of science, while others are still lacking in this aspect. It is well-known that the nature of science serves as a crucial foundation that should be applied in science education, especially in physics. This is because the nature of science plays a role as the basis to guide a more holistic learning approach and an exploratory process in understanding knowledge about the natural world. Hence, a study was conducted to analyze physics textbooks to analyze the percentage of nature of science content and describe the proportion of nature of science aspects in high school physics textbooks. The research employed a mixed methods approach, combining qualitative and quantitative research. The quantitative research section involved the development of the theory, including observations and data collection for accuracy. The quantitative research portion explained how to obtain percentage data for the ten aspects of the nature of science under investigation. The study results showed that the textbook published by Grafindo, referred to as Book B, presented the most aspects of the nature of science compared to the other two textbooks. Quotations in Book B were presented explicitly, although some quotations were presented implicitly. Books A and C were found to be less inclusive of the nature of science aspects in the measurement material. The proportion of the appearance of the nature of science in Book A was 33%, in Book B, it was 53%, and in Book C, it was 27%. Overall, all three evaluated textbooks explicitly conveyed aspects of the nature of science. The implications of this research highlight the importance of incorporating the nature of science aspects in science learning materials to enhance understanding of the nature of science, as the nature of science is a complex concept and serves as a fundamental foundation for studying science.